PENGARUH LATIHAN JALAN CEPAT BERIRAMA TERHADAP DAYA TAHAN DAN KETEPATAN LANGKAH PADA PESERTA EKSTRAKURIKULER DRUMBAND DI SMK ASSUBANDIYAH - Mahendra, Doni; Sobar; Debi Krisna Irawan; Rafdlal Saeful Bakhri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to determine whether there is an "effect of rhythmic fast walking exercise on endurance and step accuracy among drumband extracurricular participants at SMK Assubandiyah." The research method used by the author was an experiment with a One Group Pretest-Posttest design. The research population consisted of members of the Drumband extracurricular activity at SMK Assubandiyah. The sampling technique used was purposive sampling. The instrument employed was the multi-stage fitness test (beep test) to measure endurance and step accuracy. Data processing was conducted using mean, standard deviation, normality test, homogeneity test, and hypothesis testing. Based on the results of data processing and analysis, it can be concluded that there is a significant effect of "rhythmic fast walking exercise on endurance and step accuracy among drumband extracurricular participants at SMK Assubandiyah." The data processing results are as follows: Based on the analysis of Table 4.2, the normality test yielded a pretest significance value of 0.959 and a posttest significance value of 0.999. Since both values are greater than 0.05, the data are declared normally distributed. The homogeneity test in Table 4.3 showed a significance value (sig) of 0.237, which is greater than 0.05, indicating that the data are homogeneous. Based on the t-test analysis in Table 4.4, the obtained significance value (sig) was 0.000, which is less than 0.05; therefore, H1 is accepted and H0 is rejected, with a pretest mean score of 58.67 and a posttest mean score of 86.17. The data for this study were obtained and analyzed using SPSS 26.